2013
DOI: 10.3171/2013.2.spine12468
|View full text |Cite
|
Sign up to set email alerts
|

A less-invasive cervical laminoplasty for spondylotic myelopathy that preserves the semispinalis cervicis muscles and nuchal ligament

Abstract: Object Modified cervical laminoplasty techniques have been developed to reduce postoperative axial neck pain and preserve function in patients with cervical spondylotic myelopathy (CSM). However, the previous studies demonstrating satisfactory surgical outcomes had a retrospective design. Here, the authors aimed to prospectively evaluate the 2-year outcomes of a modified cervical laminoplasty technique for CSM that preserves the paravertebral muscles. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…A number of laminoplasty procedures have been developed for the treatment of CSM. Many studies have shown that the surgical outcome of laminoplasty are satisfactory131115182225). However, postoperative complications may arise, including decreased cervical ROM and loss of cervical lordotic alignment, all of which may significantly impair the quality of life4510).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of laminoplasty procedures have been developed for the treatment of CSM. Many studies have shown that the surgical outcome of laminoplasty are satisfactory131115182225). However, postoperative complications may arise, including decreased cervical ROM and loss of cervical lordotic alignment, all of which may significantly impair the quality of life4510).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several reports describing a reduction in ROM and cervical malalignment after cervical laminoplasty such as kyphosis and spondylolisthesis, and these problems remain under discussion241324). In many researches, ROM reduction is reported to range from 30% to 70% of the preoperative ROM1722).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous reports have described a reduction in ROM as well as a progression of sagittal imbalance after laminoplasty, but the etiology of these problems remain debatable [10,11]. The damage and atrophy of the posterior deep muscles including the semispinalis cervicis muscle, injury of the nuchal ligament, and bony fusion of facet joints after laminoplasty are considered the main reasons for these postoperative changes [12][13][14]. The reduction in ROM following laminoplasty is reported to range from 30-70% of the preoperative ROM [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…9,15,41,42,45,46,81,87,97 Emphasis was placed on the semispinalis cervicis, which they tried to preserve 97 or repair. 5,74,110 Furthermore, they also tried to preserve muscles that attach to the spinous processes of C-7.…”
Section: Neck Painmentioning
confidence: 99%